Interação universidade-empresa no âmbito do Instituto Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The university-industry interaction has been the subject of research in Production Engineering regarding the process of technology transfer and generation of new knowledge, in this regard the university is essential to the dissemination of knowledge, possessing features that go beyond the academic and professional, because they play an important role in the interaction with companies. Thus, this descriptive study conducted with the leaders of research groups with the aim of analyzing the university-industry interaction in the Federal University of Amazonas from the perspective of groups certificates, verifying their perception about the process of university-company, the aspects of the entrepreneurial university, the types of interactions present, the motivations and barriers encountered in the process, using the questionnaires. Thus, through the study, it was possible to visualize how the phenomenon is perceived in the Institute, the motivations that lead researchers to seek interaction and barriers that hinder the process dynamics. Therefore identified that the interaction of research groups with companies is still poorly performed , showing no strong features of the entrepreneurial university, and between groups that perform there is little interaction with companies.
Keywords: Universidade; Empresa; Interação; Motivações; Barreiras; University; Enterprise; Interaction; Motivations; Barriers; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO